Comparison of Genotypic (t-NGS) and Phenotypic Results for Mycobacterium tuberculosis Identification and Drug Susceptibility Testing (DST) against Tuberculosis - Paulina Rosa Evriarti; Yoeke Dewi Rasita; Harlindah Margawati; Sitti Fatimah Azzahra (RSUP Dr. Kariadi, 2025)
BACKGROUND: Accurate identification and drug susceptibility testing are crucial for tuberculosis eradication and treatment, but conventional methods require over four weeks to complete. Targeted Next Generation Sequencing (t-NGS) is a promising alternative that provides results in just four days, potentially replacing traditional methods. However, the concordance between genotypic and phenotypic methods has not been widely reported. AIMS: This study aims to see the concordance between phenotypic and genotypic methods for identifying Mycobacterium tuberculosis and determining drug susceptibility. METHOD: Sputum samples were collected from Balai Besar Laboratorium Kesehatan Masyarakat (BBLKM) Makassar from June 2024 until July 2024. M. tuberculosis DNA was extracted using the Qiagen DNA mini kit, amplified with Deeplex® Myc-TB by Genoscreen, and prepared with Illumina DNA Prep. t-NGS was performed on the MiSeq Illumina platform, and sequencing results were analyzed with Deeplex® Myc-TB by Genoscreen. A comparison of genotypic and phenotypic results (Culture and Drug Sensitivity Test) was conducted using SPSS. RESULT: Discrepancies were noted between phenotypic and genotypic results for two samples (Samples 16 and 18), where phenotypic results indicated non-tuberculous mycobacteria (NTM) and genotypic results identified M. tuberculosis. These discrepancies were not statistically significant (p>0,05). Additionally, a minor discrepancy was observed in isoniazid results for one sample (Sample 2), but the statistical result is not significance (p>0.05). CONCLUSION: t-NGS is a promising alternative to conventional methods due to its shorter testing time and capability to identify novel mutations, with discrepancies compared to phenotypic results being statistically insignificant. However, its higher cost and the need for specialized expertise limit its accessibility to some laboratories.